2023
DOI: 10.1093/llc/fqad055
|View full text |Cite
|
Sign up to set email alerts
|

Cultural specificities of online dictionaries for English learners: Evidence from a user survey and a multimodal discourse analysis

Shuneng Zhong,
Xiqin Liu

Abstract: This study examines three popular e-dictionary platforms using a quantitative user survey coupled with a qualitative multimodal discourse analysis (MDA): Chinese Youdao, Cambridge English-Mandarin Chinese Dictionary (Cambridge), and the Free Dictionary (FD). The survey (N = 478) revealed that, despite its language flaws, Youdao was preferred by most Chinese EFL (English as a Foreign Language) learners mainly due to its search functionality and personalization. In contrast, English majors and postgraduates pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…As Zhong and Liu (2023) pointed out, most Chinese EFL (English as a foreign language) learners favored Youdao Machine Translation owing to its practical search functionality and personalized features. Lan and Zhao (2021) also demonstrated that Youdao Machine Translation excels in rendering distinctive Chinese expressions more effectively, benefiting from its reliance on a Chinese Internet-based database.…”
Section: Comparative Reviewmentioning
confidence: 99%
“…As Zhong and Liu (2023) pointed out, most Chinese EFL (English as a foreign language) learners favored Youdao Machine Translation owing to its practical search functionality and personalized features. Lan and Zhao (2021) also demonstrated that Youdao Machine Translation excels in rendering distinctive Chinese expressions more effectively, benefiting from its reliance on a Chinese Internet-based database.…”
Section: Comparative Reviewmentioning
confidence: 99%